2017
DOI: 10.1093/jisesa/iex031
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Molecular Characterization of the Transformer Gene From Bactrocera cucurbitae (Diptera: Tephritidae)

Abstract: transformer (tra) is a switch gene of sex determination in many insects, particularly in Dipterans. However, the sex determination pathway in Bactrocera cucurbitae (Coquillett), a very destructive pest on earth, remains largely uncharacterized. In this study, we have isolated and characterized one female-specific and two male-specific transcripts of the tra gene (Bcutra) of B. cucurbitae. The genomic structure of Bcutra has been determined and the presence of multiple conserved Transformer (TRA)/TRA-2 binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…In B. dorsalis , the tra homologue Bdtra serves as a genetic switch in early embryonic development via the alternative sex‐specific splicing cascade to determine the sexual fate . The genomic structure and sex‐specific splicing pattern of Bdtra are similar to those found in other tephritid pests, such as Ceretitis capitata , B. oleae , Anastrepha oblique , Anastrepha suspensa , B. tryoni and B. jarvisi and B. cucurbitae . Moreover, disturbance of the tra gene mediated by RNA interference in early embryonic development resulted in sexual reversal from an XX female to an XX pseudomale, suggesting possible application in pest control.…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…In B. dorsalis , the tra homologue Bdtra serves as a genetic switch in early embryonic development via the alternative sex‐specific splicing cascade to determine the sexual fate . The genomic structure and sex‐specific splicing pattern of Bdtra are similar to those found in other tephritid pests, such as Ceretitis capitata , B. oleae , Anastrepha oblique , Anastrepha suspensa , B. tryoni and B. jarvisi and B. cucurbitae . Moreover, disturbance of the tra gene mediated by RNA interference in early embryonic development resulted in sexual reversal from an XX female to an XX pseudomale, suggesting possible application in pest control.…”
Section: Introductionmentioning
confidence: 56%
“…The wild‐type (WT) oriental fruit flies used in this study were originally collected from Haidian campus of Hainan University and cultured in the laboratory at 26 °C 70% relative humidity (RH), under a 14 : 10 h light/dark photoperiod. Adults were fed with medium comprising brewer's yeast powder/cane sugar (1 : 2 w/w), and larvae were maintained on an artificial diet . Before pupation, the grown larvae were transferred to plastic boxes containing wet sand.…”
Section: Methodsmentioning
confidence: 99%
“…The structure of Zttra was similar to the structures of orthologs in dipterans, especially in tephritid species. Previous studies have shown that tra is sex‐specifically regulated by alternative splicing (Boggs et al ., 1987; Peng et al ., 2015; Luo et al ., 2017). Two male Zttra transcripts ( Zttra ‐M1 and Zttra ‐M2), which included two and three male‐specific exons, respectively, were detected.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the existence of general principles of female and male development, different species show diverse primary sex determination signals (Beye et al, 2003;Cline, 1979;Cline & Meyer, 1996;Hall et al, 2015;Krzywinska et al, 2016;Meccariello et al, 2019;Sanchez, 2010;Sharma et al, 2017). A common theme is that diverse primary signals directly or indirectly regulate the sex-specific expression of the dsx gene repeatedly via transformer (tra) homologous genes (Concha & Scott, 2009;Gempe et al, 2009;Geuverink, Kraaijeveld, et al, 2018a;Geuverink, Verhulst, et al, 2018b;Gotoh et al, 2016;Hasselmann et al, 2008;Hediger et al, 2010;Jia et al, 2016;Lagos et al, 2007;Li et al, 2013;Liu et al, 2015;Luo et al, 2017;Morita et al, 2019;Morrow et al, 2014;Pane et al, 2002;Petrella et al, 2019;Ruiz et al, 2007;Schetelig et al, 2012;Shukla & Palli, 2012;Suzuki et al, 2015;Tian & Maniatis, 1993;Verhulst et al, 2010).…”
Section: Introductionmentioning
confidence: 99%